KULTUR PESANTREN MODERN: INTEGRASI SISTEM MADRASAH DAN PESANTREN DI PONDOK MODERN GONTOR - Moh. In’ami (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2011)
This article describes and analyzes in]tegrity of school and boardingschool cultural system. The data is collected using observation, interviewand observation. In Gontor Boarding School, the students studyseveral subjects which are combined with religious knowledge. The boardingschool itself designs the learning system as a tool by giving someobligation to the students.